An Analysis Of Regulation Number 2 Of 2015 Implementation Medan City Regional Concerning Medan City Green Open Space Zoning - Harry Kurniawan; Abdiyanto, Abdiyanto; Feby Milanie (SEAN Institute, 2024)
The increase in population triggers demand for land for residence and other activities. Urban spatial planning often lags behind increasing physical development needs, causing uncontrolled expansion of urban development and causing limited green open space. Urban green open spaces are very important for environmental sustainability, including maintaining ecosystem balance, improving air quality, and providing social space. However, the allocation of green open space in the 2015-2035 Medan City spatial planning regulations is still below the 20% target, only reaching 11.10%. Conflicts regarding permits for the use of built-up land as green open space are a frequent problem. The disclosure of empirical facts about the dynamics of the implementation of the green open space plan in Medan City can be a more comprehensive input for the Medan City Government in the 2015-2035 Medan City RDTR Revision and become a consideration for the districts/other cities to plan green open space that is fair and provides additional insight for academics, practitioners and the general public. The research uses descriptive-qualitative methods on empirical facts with spatial exploration based on the Geographic Information System using the ArcGIS 10.8 application and the Google Maps Platform to identify and analyze the realization of the implementation of green open space plans which provide various empirical facts. Data analysis is carried out spatially through technical interpretation of satellite images and overlays on several spatial research themes.The results of this paper show that the green open space plan in Medan City is dominated by undeveloped land, such as 28.50% of ponds/ponds which are not land with green open space functions, and can create dynamics in the provision of green open space. Strategies for resolving green open space problems include optimizing land acquisition, controlling urbanization, regulating land price speculation, public education, and developing green open space to mitigate environmental impacts, and involve the formation of special teams, periodic evaluations, and strong public participation.